The Success of Smoking Cessation Treatments: The Gulhane Experience - Arslan, Yakup; Öcal, Nesrin; Çağın, Ahmet; Doğan, Deniz; Taşçı, Cantürk (Addicta: The Turkish Journal on Addictions, 2021)
This study aimed to evaluate the success and factors that affected the success of smoking cessation treatments adopted in the Gulhane Smoking Cessation Polyclinic (SCP). The smokers admitted to SCP from January 1, 2018, to July 15, 2019, were included in the study. The participants were treated with varenicline or nicotine replacement therapy (NRT) combined with cognitive behavioral therapy (CBT). The number of all participants was 598, and 196 (32.8%) of them quitted smoking successfully. The varenicline group (n=264) had significantly higher number and percentage of participants who successfully quit smoking than the NRT group (n=334), which accounted for 113 (42.8%) and 83 (24.9%), respectively (p